Antisipasi Perselingkuhan Dalam Upanisad Sebagai Aktualisasi Diri Umat Beragama - Ni Putu Sri Marhaeni Diastini (Jurnal Penelitian Agama Hindu, 2019)
The most susceptible case which happen in a household this time is infidelity, this thing even become the most scary specter in a household life. Relation of husband and wife is not the only thing that be broken, the most unfortunate victims are the children who were born in family living that should be given the main affection. That case will be anticipated by ‘Upanisad’ which be base to avoid the infidelity. Upanisad is scripture which discuss about the virtue of ‘Brahman’, trip of ‘Atman’, until going to mortality. Teachings of Upanisad were made for a guidance of self actualization of religious peoples to anticipate the infidelity.